The top 100 most-cited papers in pheochromocytomas and paragangliomas: A bibliometric study - Duan, Sai-Li; Qi, Lin; Li, Ming-Hao; Liu, Long-Fei; Wang, Yong; Guan, Xiao (Frontiers in Oncology, 2022)
Background: The purpose of this study was to define and analyze the characteristics of the top 100 most-cited articles and reviews in the topic of pheochromocytomas and paragangliomas by using bibliometric methods. Methods: We explored the Web of Science Core Collection database to gather the 100 top-cited original articles and reviews of PPGL from 1985 to 2020 on December 20, 2020. We conducted a bibliometric study to identify the most influential journals, authors, countries, and institutions in the PPGL field. Results: The 100 top-cited papers were cited a total number of 25723 times, ranging from 131 to 1144 (mean: 257.23±173.64); All of these 100 top-cited papers were published between 1999 and 2017, and the number of top-cited papers published before 2008 (1999-2008) was significantly higher than that after 2008 (2009-2017) (P = 0.043); The journal with the highest number of published papers is JOURNAL OF CLINICAL ENDOCRINOLOGY & METABOLISM (n = 23); The United States of America (USA) was the most productive country in this topic which published about half of these publications (n = 51). The National Institutes of Health (NIH) had the largest number of publications (n = 17). Genes or genetics were still the hottest topic in the field of PPGLs. Conclusions: We defined and analyzed the top 100 most-cited papers in the field of PPGLs by gathering detailed information. These data provided insights into the most influential studies related to PPGL. We hoped to inspire researchers and readers in this filed to improve their understanding of PPGL research trends and provide ideas for future research from unique perspectives.